Induction of apoptosis by genipin inhibits cell proliferation in AGS human gastric cancer cells via Egr1/p21 signaling pathway. Issue 19 (1st October 2015) - Ko, Hyeonseok; Kim, Jee Min; Kim, Sun-Joong; Shim, So Hee; Ha, Chang Hoon; Chang, Hyo Ihl
Graphical abstract: Abstract: Natural compounds are becoming important candidates in cancer therapy due to their cytotoxic effects on cancer cells by inducing various types of programmed cell deaths. In this study, we investigated whether genipin induces programmed cell deaths and mediates in Egr1/p21 signaling pathways in gastric cancer cells. Effects of genipin in AGS cancer cell lines were observed via evaluation of cell viability, ROS generation, cell cycle arrest, and protein and RNA levels of p21, Egr1, as well as apoptotic marker genes. The cell viability of AGS cells reduced by genipin treatment via induction of the caspase 3-dependent apoptosis. Cell cycle arrest was observed at the G2/M phase along with induction of p21 and p21-dependent cyclins. As an upstream mediator of p21, the transcription factor early growth response-1 (Egr1) upregulated p21 through nuclear translocation and binding to the p21 promoter site. Silencing Egr1 expression inhibited the expression of p21 and downstream molecules involved in apoptosis. We demonstrated that genipin treatment in AGS human gastric cancer cell line induces apoptosis via p53-independent Egr1/p21 signaling pathway in a dose-dependent manner.